THE USE OF EVERYONE IS A TEACHER HERE METHOD TO IMPROVE STUDENTS’ SPEAKING SKILL - Eka Permatasari; Abdul Kamaruddin; Mashuri Mashuri (Tadulako University, 2022)
The objective of this research is to investigate whether or not the students’ speaking ability can improve through the Everyone is A Teacher Here Method in teaching speaking skill of tenth grade students at SMA Negeri 5 Palu. This research applies quasi experimental design, that used two classes, they are experimental class and control class. The research population was the tenth grade students of SMA Negeri 5 Palu which is consisted of 325 students. The samples were selected by purposive sampling technique and it was 17 students of X Mipa 6a and 16 students of X Mipa 6b. The instruments that was used to collect the data was tests. The tests include pre-test and post-test, with the pre-test mean score 35.29 for experimental class and 35.63 for control class. While post-test mean score is 45.29 for experimental class and 37.50 for control class. The result of the data is analyzed statistically by applying the t-test formula. The result of the data analysis show that the value of t-counted is 2.45. Applying the degree of freedom 31 (Nx + Ny – 2 = 17 + 16 – 2) and 0.05 level of significance the value of t-table is 1.567. The calculation show that the t-test value is higher than the t-table value. It means that the hypothesis of this research is accepted. It affirms that Everyone is A teacher Here Method can improve students’ speaking skill of the tenth grade students at SMA Negeri 5 Palu.